(untitled) (Scientific journal of the Fergana State University, 2025)
The article is dedicated to the analysis of flood and mudflow events formed in the Northern Fergana region. The study focuses on analyzing statistical data on mudflows observed throughout the year, as well as the formation of different types of mudflow currents, including muddy, muddy-sediment, and mud-rock flows. The genesis of mudflows is examined based on various factors such as snow and glacier melt, snow-rain, rainfall, and groundwater, along with an analysis of regional indicators. Additionally, the article analyzes the annual distribution of mudflows in certain river basins of the Northern Fergana region, considering their formation in relation to the catchment area.